181k views
1 vote
B = 1/2 a - 3c rearrange to make a the subject

2 Answers

0 votes

Explanation:


b = (1)/(2) a- 3c

Multiply both sides ✖ of the equation by 2


2b = a - 6c

Move the variable to the left-hand side and change its sign


- a + 2b = - 6c

MOVE THE VARIABLE TO THE RIGHT-HAND SIDE AND CHANGE ITS SIGN


- a = - 6c - 2b

Change the sign on both sides of the equation


a = 6c + 2b

Therefore the answer is


a = 6c + 2b

User Ethan Fischer
by
5.5k points
4 votes

Answer:


\huge \boxed{a = 2b + 6c}

Explanation:

b = 1/2a - 3c

Add 3c to both sides of the equation.

b + 3c = 1/2a - 3c + 3c

b + 3c = 1/2a

Switch sides.

1/2a = b + 3c

Multiply both sides of the equation by 2.

2(1/2a) = 2(b + 3c)

a = 2b + 6c

User VoonArt
by
6.0k points